Inactivation of phoPQ genes attenuates Salmonella Gallinarum biovar Gallinarum to susceptible chickens - Rodrigues Alves, Lucas Bocchini [UNESP]; Neto, Oliveiro Caetano de Freitas; Batista, Diego Felipe Alves [UNESP]; Barbosa, Fernanda de Oliveira [UNESP]; Rubio, Marcela da Silva [UNESP]; de Souza, Andrei Itajahy Secundo [UNESP]; Almeida, Adriana Maria de [UNESP]; Barrow, Paul Andrew; Junior, Angelo Berchieri [UNESP] (Springer Nature, 2018)
Salmonella Gallinarum is a host-restrict pathogen that causes fowl typhoid, a severe systemic disease that is one of the major concerns to the poultry industry worldwide. When infecting the bird, SG makes use of evasion mechanisms to survive and to replicate within macrophages. In this context, phoPQ genes encode a two-component regulatory system (PhoPQ) that regulates virulence genes responsible for adaptation of Salmonella spp. to antimicrobial factors such as low pH, antimicrobial peptides and deprivation of bivalent cations. The role of the mentioned genes to SG remains to be investigated. In the present study a phoPQ-depleted SG strain (SG ΔphoPQ) was constructed and its virulence assessed in twenty-day-old laying hens susceptible to fowl typhoid. SG ΔphoPQ did cause neither clinical signs nor mortality in birds orally challenged, being non-pathogenic. Furthermore, this strain was not recovered from livers or spleens. On the other hand, chickens challenged subcutaneously with the mutant strain had discreet to moderate pathological changes and also low bacterial counts in liver and spleen tissues. These findings show that SG ΔphoPQ is attenuated to susceptible chickens and suggest that these genes are important during chicken infection by SG.
Keywords: Adaptation; Chickens; Fowl typhoid; Mutation; Virulence